Microalgae: A potential bioagent for treatment of emerging contaminants from domestic wastewater - Sanjeet Mehariya (8737758) (2024)
Water crisis around the world leads to a growing interest in emerging contaminants (ECs) that can affect human health and the environment. Research showed that thousands of compounds from domestic consumers, such as endocrine disrupting chemicals (EDCs), personal care products (PCPs), and pharmaceuticals active compounds (PhAcs), could be found in wastewater in concentration mostly from ng L−1 to μg L−1. However, generally, wastewater treatment plants (WWTPs) are not designed to remove these ECs from wastewater to their discharge levels. Scientists are looking for economically feasible biotreatment options enabling the complete removal of ECs before discharge. Microalgae cultivation in domestic wastewater is likely a feasible approach for removing emerging contaminants and simultaneously removing any residual organic nutrients. Microalgal growth rate and contaminants removal efficiency could be affected by various factors, including light intensity, CO2 addition, presence of different nutrients, etc., and these parameters could greatly help make microalgae treatment more efficient. Furthermore, the algal biomass harvests could be repurposed to produce various bulk chemicals such as sustainable aviation fuel, biofuel, bioplastic, and biochar; this could significantly enhance the economic viability. Therefore, this review summarizes the microalgae-based bioprocess and their mechanisms for removing different ECs from different wastewaters and highlights the different strategies to improve the ECs removal efficiency. Furthermore, this review shows the role of different ECs in biomass profile and the relevance of using ECs-treated microalgae biomass to produce green products, as well as highlights the challenges and future research recommendations. Other Information Published in: Chemosphere License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.chemosphere.2024.141245